Penyediaan format isian berbasis komputer untuk pencatatan pendistribusian bahan bakar minyak bersubsidi di SPBU-N Koperasi Perikanan Pantai Madani Kabupaten Bengkalis - Miswadi Miswadi; Romie Jhonnerie; Yossi Oktorini (Unri Conference Series: Community Engagement, 2019)
The cooperative of Perikanan Pantai Madani is the institution of a public refueling station for fishermen (SPBU-N) who distributes subsidized diesel fuel for fishing activities in the Pambang Pesisir Village and surrounding areas. All purchases transactions were implemented manually and used common counting tool and recounts occur to retrieve information for the needs of monthly and annual reports. This empowerment aimed to provide convenienced for SPBU-N manager due to gain information for recapitulation of subsidized fuel distribution, and the daily (monthly) and annual stock reports to PT Pertamina can be delivered on time, confidently. The mothods used were presentation, technical guidance and monitoring. The result of these activities were the availability of a standard form which developed from real transaction data (2014-2018). The SPBU-N manager has used the form provided and recorded the distribution of subsidized fuel oil for 2019, which made easier for the manager obtained the information needed for reporting since daily records have been integrated with the monthly and annual report information needs.